2020
DOI: 10.5812/jkums.108939
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance of Pseudomonas aeruginosa Strains in the Patients Admitted to Imam Reza Hospital in Kermanshah, Iran (2016-2018)

Abstract: Background: Nosocomial infections are important medical concerns in developed and developing countries. Pseudomonas aeruginosa is considered the third leading cause of nosocomial infections following Staphylococcus aureus and Escherichia coli. Objectives: The present study aimed to determine the antibiotic resistance of isolated P. aeruginosa strains in the patients admitted to Imam Reza Hospital in Kermanshah, Iran. Methods: This descriptive, cross-sectional study was conducted on 900 patients with positive P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
2
0
0
Order By: Relevance
“…Therefore, these antibiotics are not good choices for the empiric treatment of suspected P. aeruginosa infections in Iran. Other similar studies in Iran, India, and Brazil have shown similar results (2,20,21). This study had a limitation in determining the antibacterial susceptibility of isolates for all classes of antibiotics.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Therefore, these antibiotics are not good choices for the empiric treatment of suspected P. aeruginosa infections in Iran. Other similar studies in Iran, India, and Brazil have shown similar results (2,20,21). This study had a limitation in determining the antibacterial susceptibility of isolates for all classes of antibiotics.…”
Section: Discussionsupporting
confidence: 67%
“…However, the sensitivity of the strains to this drug was low in patients hospitalized in ICU (about 40%). Similar studies in Brazil, Iran, and India have reported the low susceptibility of P. aeruginosa isolates to tobramycin (32 -42%) (20)(21)(22).…”
Section: Discussionsupporting
confidence: 54%